The Impact of Mandatory Food-Marketing Regulations on Purchase and Exposure: A Narrative Review - Alanoud Alfraidi; Nora Alafif; Reem Alsukait (MDPI AG, 2023)
(1) Background: Several governments have enforced a series of actions to improve the local food environment and reduce obesity-related diseases in the population by implementing statutory regulations to reduce or ban the marketing of products that are considered unhealthy based on nutrient profile systems or them being high in fat, sugar, and salt (HFSS); (2) Objective: This narrative review is aiming to provide a comprehensive exploration of the available evidence on the impact of identified mandatory regulations restricting food marketing, including advertisements and packages on the exposure and purchase of HFSS food products, to help justify the need for these regulations; (3) Methods: Articles were retrieved by searching electronic databases, including EBSCO Education, PubMed, Scopus, Web of Science, and Google Scholar from 2012 up to December 2022; (4) Results: A total of 12 articles were included in this review. Almost all mandatory food-marketing regulations have evidence in favor of reducing HFSS food purchases and exposure; (5) Conclusions: Protecting children and adolescents from food and beverage marketing through mandatory regulations is a crucial step toward tackling global childhood and adolescent obesity and securing a healthier environment for future generations.